(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione: per un pluralismo “ragionevole” di fronte ai mutamenti sociali - 2. Dalla teoria alla pratica: alcuni aspetti della “questione” islamica nelle contraddizioni politiche e giuridiche del presente - 3. Una premessa di metodo: la libertà religiosa nel modello democratico costituzionale. Aporie persistenti e spunti di riforma (ma siamo ancora agli inizi) - 4. Diritto fondamentale alla moschea vs “Registro pubblico delle moschee” - 5. Un Albo per gli imam (e altre cose) - 6. Conclusioni. Religious Freedom and the right of Muslim communities. Some critical remarks on two recent draft laws on mosques and imams ABSTRACT: This contribution starts from the proposal of two draft laws on Islam in Italy (one on the legal status of mosques and the other on imams), which deal with concrete issues that the country faces, taking into consideration the multicultural context of Italy. So far, the approach of the Italian political class has been quite conservative and not willing to take into account possible solutions offered by the Constitution, such as the protection of basic human rights. The solutions have been more focused on the potential lack of trust towards Muslim communities and on legal solutions not fully integrated within a wider European approach. The proposed solutions appear therefore to be more the result of ad hoc approaches, influenced by considerations of real politik, than tools fully in line with the requirements of the Constitutional protection of human rights.